Kunst im öffentlichen Raum - Kassel 1950-1991. - Bromig, Christian; Dobe, Hans-Jürgen; Georgsdorf, Heiner; Heinz, Marianne; Hülbusch, Karl Heinrich; Nieder, Horst; Nordhoff, Hans-Bernhard; Raacke, Walter; Schmidt, Ulrich; Schuchard, Jutta; Werckmeister, Johanna (Kassel Marburg : Jonas Verlag für Kunst und Literatur Kulturamt Kassel, 1991)
Andrian, Dieter Freiherr von ; Austad, Magne ; Baumann, Horst H. ; Berg, Michael ; Berger, Günther ; Beuys, Joseph ; Blase, Karl Oskar ; Blume, Claudia ; Bornes, Giesela ; Brinckmann, Helmut ; Bronisch, Paul ; Brummack, Heinrich ; Burek, Vincent ; Cüppers, Albert ; Delsing, Bernard ; Demnig, Gunter ; Deventer, Friedel ; Dieterich, Jörg ; Döbel, Carl ; Drüke, Karl ; Fiebig, Eberhard ; de Figueiredo, Márcia ; Fingerling, K.H. ; Goetz, Borris ; Gormley, Antony ; Gräsel, Friedrich ; Grünwald, Walter ; Grzimek, Waldemar ; Hainke, Wolfgang ; Heinemann, Günther ; Hemrich, Heinz ; Hertha, Peter ; Hoheisel, Horst ; Holschuh, Jan ; Holzer, Jenny ; Hölzinger, Johannes Peter ; Horák, Petr ; Hugues, Wilhelm ; Huster, Victor ; Jaekel, Hildegard ; Jaritz, Horst ; Kaiser, Stefan ; Katase, Kazuo ; Kirchner, Heinrich ; Kissel, Rolf ; Klingelhöfer, Sascha ; Knudsen, Knud ; Kreutz, Heinz ; Krömeke, Werner ; Krönung, Bernhard ; Kunze, Uwe ; Lehmann, Kurt ; Maier, Lothar ; de Maria, Walter ; Meier, Dieter ; Michel, Oswald ; Nele, E.R. ; Nikusch, Walter ; Noell, Werner ; Olbrich, Jürgen O. ; Oldenburg, Claes ; Pohl, Hermann ; Prüstel, Heinz ; Pütz, Alfred ; Redeker, Werner ; Reinhold, Johannes ; Rieder, Andreas ; Rohleder, Hugo ; Roth, Georg ; Röttger, Ernst ; Rückriem, Ulrich ; Rudolph, Dieter ; Sauerland, Josef ; Sautter, Hans ; Schamrette, Arnold ; Sidur, Vadim ; Siegele, Sigrid ; Sinken, Hein ; Sommerlad, E.L. ; Sprangenberg, Gerda ; Spreng, Blasius ; Steffens, Karl-Max ; Sturm, Robert ; Theimer, Ivan ; Thiel, Maarten ; Traudtmann, Rudolf ; Viani, Alberto ; Weber, Rolf ; Weiser, Christian ; Wiegand, Erika Maria ; Wiegel, Heinz ; Wittig, Gustav ; Wolf, Karl Adalbert ; Wolff, Alejandra ; Wünsche, Jochen ; Wüpper, Heinz Detlef ; Zach, Thomas ; Zander, Alfred ; etc.
Biog. per kunstenaar
boek
Keywords: Kassel